Red tape and corruption along ECOWAS trade corridors - Bouët, Antoine; Cissé, Brahima; Sy, Abdourahmane; Traoré, Fousseini (Association Ouest Africaine du Commerce Transfrontalier des produits Alimentaires, Agro-sylvo-pastoraux et Halieutiques, 2021)
This paper presents an initiative to collect data on the red tape and corruption that affect cross-border trade in food and agricultural products along ECOWAS (Economic Community of West African States) trade corridors. Between 2015 and the first quarter of 2020, data on the number of checkpoints set up, the time lost at each checkpoint, and the value of illicit payments made by transporters to officials were collected on 14 trade corridors. We present descriptive statistics of this base and then estimate the ad valorem equivalent of these payments and time lost. In 2019 these corresponded to an ad valorem tax of 1.41 percent. The loss of time fits well with the definition of administrative barriers and corresponds to an ad valorem tax of 0.11 percent. Illegal payments constitute corruption and are equivalent to a 1.31 percent tax for transporters. The dispersion of ad valorem equivalents is significant from one corridor to another, and from one year to another. For example, in the first quarter of 2020, these practices were equivalent to a tax of 22.6 percent on the corridor linking Abidjan in Côte d'Ivoire to Lagos in Nigeria. Finally, we make policy recommendations. These recommendations should take into account the environment in which these practices take place. Increasing transparency by communicating these practices and regulations is a priority in the short and medium term